A STUDY OF METHOD DEVELOPMENT, VALIDATION AND FORCED DEGRADATION FOR SIMULTANEOUS QUANTIFICATION OF CABOZANTINIB AND NIVOLUMAB IN BULK AND PHARMACEUTICAL DOSAGE FORM BY RP-HPLC - K, GOPINATH; M, YANADIRAO; Y, PAVANI; RAO M, SUBBA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present paper describes a simple, accurate, and precise reversed-phase high-performance liquid chromatography (HPLC) method for rapid and simultaneous quantification of cabozantinib (CZT) and nivolumab (NVM) in bulk and pharmaceutical dosage form. Methods: The chromatographic separation was achieved on Luna C18 (150 mm×4.6 mm, 3.5 μm). Mobile phase contained a mixture of 0.1% orthophosphoric acid and acetonitrile in the ratio of 50:50 v/v, flow rate 1.0 ml/min, and ultraviolet detection at 222 nm. Results: The proposed method shows a good linearity in the concentration range of 20–300 μg/ml for CZT and 5–75 μg/ml for NVM under optimized conditions. Precision and recovery study results are in between 98 and 102%. In the entire robustness conditions, percentage relative standard deviation is <2.0%. Degradation has minimum effect in stress condition and solutions are stable up to 24 h. Conclusion: This method is validated for different parameters such as precision, linearity, accuracy, limit of detection (LOD), limit of quantification (LOQ), ruggedness, robustness, and forced degradation study were determined according to the International Conference of Harmonization (ICH) Q2B guidelines. All the parameters of validation were found to be within the acceptance range of ICH guidelines. Since there is no HPLC method reported in the literature for the estimation of CZT and NVM in pharmaceutical dosage forms, there is a need to develop quantitative methods under different conditions to achieve improvement in sensitivity, selectivity, etc. The author declares the interest to develop a validation and forced degradation for simultaneous quantification of CZT and NVM.